Neural correlates of irony comprehension: Role of schizotypal personality traits in healthy subjects and schizophrenia - Rapp, A.M.; Langohr, K.; Mutschler, D.E. (Personality and individual differences, 2014)
Background: Recent work indicates inter-individual differences in schizotypal personality traits are associated with performance in comprehending nonliteral language such as irony and metaphors. Comprehension of nonliteral conversational remarks is known to be impaired in schizophrenia. We investigated the influence of schizotypal personality traits, measured with the SPQ, on the comprehension of ironic expressions in healthy subjects and patients with schizophrenia using functional magnetic resonance imaging. Methods: 15 female patients with DSM IV schizophrenia and 15 matched healthy female control subjects read ironic and literal text vignettes during a functional magnetic resonance imaging scan. Results: Performance and BOLD response in the anterior cingulate and right hemisphere temporal regions showed a negative correlation with the SPQ across all subjects. Conclusions: We conclude that decreased BOLD response in both language comprehension and theory of mind networks is associated with schizotypal personality traits, although several limitations must be considered.